Injectable hyaluronic acid-based hydrogel niches to create localized and time-controlled therapy delivery - Veronica Torresan; Alessandro Gandin; Paolo Contessotto; Francesca Zanconato; Giovanna Brusatin (Materials Today Bio)
The use of hydrogel-based niches for therapy delivery enables the concentration of active components and cells in a targeted area. This approach enhances efficacy while minimizing systemic side effects by spatially controlling the release of the therapy. Precise tuning of the matrix's chemical properties and control of both material degradation and release profile of biologically active components are required to reduce the optimal dose and extend its therapeutic effect. Here we aimed to develop an injectable hydrogel that can fulfill all these requirements. We designed a system based on hyaluronic acid, crosslinked via click-reaction with multi-arm polyethyleneglycol and functionalized with RGD peptides. Additionally, we incorporated thiol-modified heparin into the formulation, which provides specific binding sites for cytokines. Our results indicate that heparin incorporation can delay cytokine release, while the release of nanocarriers can be regulated by adjusting the crosslinking degree. This design modulates pore size and degradation time, while preserving the injectability of the niche. In conclusion, this system offers a versatile and efficient delivery platform suitable for therapeutic applications in a wide range of diseases.